2014
DOI: 10.1103/physrevb.89.100402
|View full text |Cite
|
Sign up to set email alerts
|

Weak spin interactions in Mott insulating La2O2Fe2OSe2

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(96 citation statements)
references
References 45 publications
27
63
0
Order By: Relevance
“…Significant anisotropic peak broadening of magnetic Bragg reflections was observed for both Ce and Nd phases, similar to that observed for La 2 O 2 Fe 2 OSe 2 [25]. This could be modeled with an expression for antiphase boundaries perpendicular to the c axis [34,35], which gave a significantly improved fit to the data (Fig.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Significant anisotropic peak broadening of magnetic Bragg reflections was observed for both Ce and Nd phases, similar to that observed for La 2 O 2 Fe 2 OSe 2 [25]. This could be modeled with an expression for antiphase boundaries perpendicular to the c axis [34,35], which gave a significantly improved fit to the data (Fig.…”
Section: Resultssupporting
confidence: 60%
“…Interestingly, a similar 2-k model, composed of perpendicular AFM chains, has been predicted for the FeAs sheets in iron arsenides and oxyarsenides [27,28]. The recent studies on La 2 O 2 Fe 2 OSe 2 indicated the presence of antiphase boundaries or stacking faults perpendicular to the stacking direction and gave evidence for 2D-Ising-like magnetism within these sheets [25]. In the light of this work, it is timely to report a similar analysis on Ln 2 O 2 Fe 2 OSe 2 (Ln = Ce, Nd) analogs to test the robustness of the 2-k model to changes in Fe-O bond lengths and to a magnetic moment on the Ln site.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Indeed, superconductivity was found to border a Mott insulating phase in alkaline iron selenides A 1−x Fe 2−y Se 2 (the "245" family, with A = K, Rb, Cs, or Tl) [24][25][26][27] . The Mott insulating ground state has also been identified in the iron oxychalcogenides La 2 O 3 Fe 2 (Se,S) 2 [28,29], R 2 O 3 Fe 2 Se 2 (here R = Ce,Pr,Nd,Sm) 30 , and Sr 2 F 2 Fe 2 OS 2 [31]. Further evidence in favor of proximity to the incipient Mott phase comes from the suppression of the Drude peak in optical conductivity measurements on iron pnictides 32,33 and the spectral weight transfer induced by temperature 34,35 .…”
Section: Introductionmentioning
confidence: 99%